Manajemen Pengembangan Program Pembelajaran Pendidikan Islam Di SD Negeri 060857 - Aina Ul-Mardiyah Ray; Amiruddin Siahaan; Aji Pramudya; Laila Ali Tanjung; Okta Elviana Manurung; Zuchairunnisa . (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of the research was to find out how to describe planning for the development of Islamic education learning programs, to find out how to describe the implementation of developing Islamic education learning programs, and to describe the evaluation process in developing Islamic education learning programs as well as the follow-up process in developing Islamic education learning programs at SD NEGERI 060857 school This type of research uses qualitative methods. Data collection techniques are carried out by observation, interviews, and documentation. The results of the management research on the development of Islamic education learning programs at SD NEGERI 060857 are a systematic process carried out by the teacher. The steps are the preparation of subject matter, the use of teaching media, the use of method and assessment approaches. Its development is the process of implementing teaching and learning in the classroom. Implementation of the evaluation is the result of the effectiveness of learning outcomes. Follow-up activities are a learning process. These activities include; giving assignments, enriching material, providing extracurricular motivation (mandatory congregational prayers, skills in the art of reading the Koran, skills in calligraphy and participating in religious competitions).